2021
DOI: 10.1021/acschemneuro.1c00395
|View full text |Cite
|
Sign up to set email alerts
|

Site of Cholesterol Oxidation Impacts Its Localization and Domain Formation in the Neuronal Plasma Membrane

Abstract: Cholesterol is integral to the structure of mammalian cell membranes. Oxidation of cholesterol alters how it behaves in the membrane and influences the membrane biophysical properties. Elevated levels of oxidized cholesterol are associated with neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, and Huntington’s disease. Previous work has investigated the impact of oxidized cholesterol in the context of simple model membrane systems. However, there is a growing body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
(205 reference statements)
0
7
0
Order By: Relevance
“…Structural analysis of both types of oxidation revealed that oxysterols with oxidized tails have a similar effect on membrane fluidity as normal cholesterol. They increase the order of phospholipids, reduce lateral diffusion, and decrease membrane fluidity [ 115 , 122 ]. Tail-oxidized cholesterol mostly orients parallel to the bilayer normal in each leaflet, with its hydroxyl group positioned toward the head groups of phospholipids near the water interface.…”
Section: Non-reactive MD Simulations Of Lipid Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural analysis of both types of oxidation revealed that oxysterols with oxidized tails have a similar effect on membrane fluidity as normal cholesterol. They increase the order of phospholipids, reduce lateral diffusion, and decrease membrane fluidity [ 115 , 122 ]. Tail-oxidized cholesterol mostly orients parallel to the bilayer normal in each leaflet, with its hydroxyl group positioned toward the head groups of phospholipids near the water interface.…”
Section: Non-reactive MD Simulations Of Lipid Membranesmentioning
confidence: 99%
“…Tail-oxidized cholesterol mostly orients parallel to the bilayer normal in each leaflet, with its hydroxyl group positioned toward the head groups of phospholipids near the water interface. In contrast, oxysterol with an oxidized ring behaves somewhat differently than normal cholesterol [ 122 ]. It induces a greater tilt angle in membrane phospholipids and significantly disrupts membrane structure compared to tail-oxidized and normal cholesterols [ 115 , 122 ].…”
Section: Non-reactive MD Simulations Of Lipid Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…36−39 Cholesterol oxidation is associated with neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, multiple sclerosis, and Huntington's disease. 40 Changing the concentration of phosphatidylethanolamine lipids and cholesterol alters rhodopsin equilibrium, demonstrating the effects of membrane lipid composition on this key model GPCR. 41−44 We have previously demonstrated that both 5-HT 1A R and A 2A R will localize to phase-separated domains in a membrane in a composition-dependent manner.…”
Section: ■ Introductionmentioning
confidence: 99%
“…GPCR function is known to be coupled to the composition of the plasma membrane. For instance, it is well documented that changes in membrane cholesterol homeostasis lead to several GPCR-related disease pathologies. , Additionally, cholesterol oxidation affects its localization and membrane biophysical properties, leading to membrane thinning, increased permeability, and reduced lipid order. Cholesterol oxidation is associated with neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, and Huntington’s disease . Changing the concentration of phosphatidylethanolamine lipids and cholesterol alters rhodopsin equilibrium, demonstrating the effects of membrane lipid composition on this key model GPCR. We have previously demonstrated that both 5-HT 1A R and A 2A R will localize to phase-separated domains in a membrane in a composition-dependent manner. , We have also shown that the functional activity of 5-HT 1A R depends on membrane order .…”
Section: Introductionmentioning
confidence: 99%